Impulse Power Supplies: General Trends and Benefits - Docent. Khaidarov A.H; Docent. Eltazarov B.T.; Sen.Lec. Kimizbaeva A.E. (Genius Journals, 2022)
The article is devoted to research and analysis of the state of the power supply market. General trends in the development and optimization of their parameters are revealed, and the advantage of switching power supplies is also substantiated. Samples of modern efficient network adapters and uninterruptible power supplies are given.
Keywords: Power supply; network adapter; uninterruptible power supply; switching power supply